Changes in Maternal Glucose Metabolism after the Administration of Dexamethasone for Fetal Lung Development. (25th March 2012) - Jian Yun, Xu; Zhaoxia, Liang; Yun, Chai; Qin, Fang; Yuanyuan, Chen; Danqing, Chen
Abstract : Aims . Antenatal dexamethasone administration for fetal lung development may impair maternal glucose tolerance. In this study, we investigated whether glucose and insulin levels differed among singleton and twin pregnancies and pregnancies with impaired glucose tolerance (IGT) after treatment with dexamethasone. Methods . Singleton pregnancies, twin pregnancies, and pregnancies with IGT between 28 and 33 weeks of gestation whose mothers were treated with dexamethasone were enrolled in this study. Exclusion criteria included gestational hypertension, diabetes, renal disorders, and infectious diseases. The fasting plasma glucose and insulin levels were checked before administration and 24 h, 48 h, and 72 h after treatment was completed. Results . Mean glucose levels were significantly higher in the twin pregnancy and IGT groups at 24 h and 48 h after the administration of dexamethasone than those in the singleton pregnancy group (P < 0.05 ). Although there was no significant difference in glucose levels before administration and 72 h after dexamethasone administration among the three groups, insulin levels in the IGT group were significantly higher (P < 0.05 ). Insulin levels in the singleton pregnancy group at 24 h and 48 h after treatment were significantly lower than in the twin and IGT groups. Conclusion . The effects on maternal fasting blood glucose and insulin levels of dexamethasone administrated to promote fetal lung maturation correlated with embryo number and the presence of IGT.